2020
DOI: 10.1186/s12872-020-01422-3
|View full text |Cite
|
Sign up to set email alerts
|

Readmission rates following heart failure: a scoping review of sex and gender based considerations

Abstract: Background: Although hospital readmission for heart failure (HF) is an issue for both men and women, little is known about differences in readmission rates by sex. Consequently, strategies to optimize readmission reduction programs and care strategies for women and men remain unclear. Our study aims were: (1) to identify studies examining readmission rates according to sex, and (2) to provide a qualitative overview of possible considerations for the impact of sex or gender. Methods: We conducted a scoping revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
1
11
2
Order By: Relevance
“…These results may be associated with previously described differences in pharmacological treatment. A meta-analysis found more articles reporting that men with HF had significantly higher readmission rates compared to women ( 47 ). The effect of sex on readmission may depend on the length of follow-up, with a longer duration of follow-up favoring higher readmission rates among men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results may be associated with previously described differences in pharmacological treatment. A meta-analysis found more articles reporting that men with HF had significantly higher readmission rates compared to women ( 47 ). The effect of sex on readmission may depend on the length of follow-up, with a longer duration of follow-up favoring higher readmission rates among men.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of sex on readmission may depend on the length of follow-up, with a longer duration of follow-up favoring higher readmission rates among men. Thus, Hoang-Kim et al ( 47 ) reported that the readmission rate for men was higher when the duration of follow-up was >1 year. In contrast, women were more likely to experience higher readmission rates than men when the time to event was <1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Although HF incidence is initially higher in men, women survive longer after the onset of the disease [ 24 ]. A recent review reported that female patients with HF were more likely to experience higher readmission rates than men when the time-span was less than a year [ 27 ]. However, the female’s contribution to the prognosis of HF has frequently been underestimated in many randomized controlled trials due to the exclusion of extreme clinical variables that are dominant in females [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As per prior studies [ 16 , 17 ], diabetes mellitus, hypertension, and thyroid disease are prevalent among women, whereas AF is more frequent in men. Unfortunately, sex differences in clinical characteristics and adverse outcomes in HF patients with AF have received limited attention [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation